Common reeds (Phragmites australis) as sustainable energy source: experimental and modelling analysis of torrefaction and pyrolysis processes. Issue 4 (4th September 2012) - Patuzzi, Francesco; Mimmo, Tanja; Cesco, Stefano; Gasparella, Andrea; Baratieri, Marco
Abstract The aim of this study is to apply advanced analytical techniques and kinetic modelling to common reeds (Phragmites australis) to characterize its pyrolysis and torrefaction as possible environmental friendly and sustainable pathways of fuel upgrading. Simultaneous thermogravimetric and differential scanning calorimetry analysis have been carried out on common reeds. The evolved gases during the decomposition process have been analysed by a coupled infrared gas analyser and gas chromatograph/mass spectrometer. Different reed origins (China and Italy) and plant parts (stem and leaves) have been compared. The results have been used to calibrate a torrefaction kinetic model. The model has also been tested simulating a reed torrefaction run occurring in a bench‐scale apparatus, supplementing the chemical analysis with a thermal simulation of the reactor carried out through a finite elements approach. The results show that the proposed modelling approach allows the prediction of the reaction products with a satisfying degree of accuracy. Besides its phytodepuration potential, P. australis has proven to be an interesting natural biomass resource for thermochemical conversion processes and energy production both for its suitability and availability.